Towards a Technological Model for Effective Communication in Education: The Campus Radio Concept - B. Ubong; M. Okpor (University of Sofia, 2018)
Education as a concept can only be discussed in the context of communication. In theory and in practice, education implies transfer of knowledge which in simple terms is about coded information from one party that knows or custodies such information to another party that is the recipient of such information. Technology, seen as materials and as know-how, permeates all aspects of education, from the source (teacher or knowledge pool) to the receiver (student or learner) whether in formal or informal settings. This paper reviews the radio broadcasting system in Nigeria as a tool for mass communication. It presents a technology model for effective communication that can be applied in the specific area of radio broadcasting particularly in the developing country context where other aspects of information and communication technology are fairly rudimentary or grossly inadequate. It makes a case for compulsory Campus radio systems which are at present very few in institutions of higher learning in Nigeria because of the prohibitive cost of purchase, installation, maintenance, as well as paucity of technical personnel.